Proteomic dataset of sorghum leaf and root responses to single and combined drought and heat stress - Ali Elnaeim Elbasheir Ali; Robert E. Sharp; Laura Greeley; Scott C. Peck; David L. Tabb; Ndiko Ludidi (Scientific Data)
Abstract Drought and heat stress significantly limit crop growth and productivity. Their simultaneous occurrence, as often observed in summer crops, leads to larger yield losses. Sorghum is well adapted to dry and hot conditions. Despite the progress that has been made in determining proteomic responses to water deficit or heat stress in crops, such information remains limited for crops subjected to combined water deficit and heat stress. This study presents quantitative proteomics analyses of leaf and root tissues of two contrasting sorghum genotypes grown under normal conditions, water deficit stress, heat stress, and water deficit combined with heat stress. We identified differentially expressed proteins between the two genotypes under these different treatments. GO and KEGG annotation revealed biological processes and molecular pathways associated with sorghum responses to these treatments. Interpretation as well as integration of these proteomics data with other ‘omics’ signatures may highlight key mechanisms involved in sorghum adaptations to these stresses.